Analisis Komparasi Kinerja Pasar Modal Di Indonesia, Hongkong, China, Inggris Dan Amerika - Rahamis, Yulein (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
This study is aimed to compare the performance of the Indonesian capital market with capital markets in Hong Kong, China, Britain, and America. Comparisons are made by using the Composite Stock Price Index (CSPI) and the Market Return, the data that is used comes from Indonesia Stock Exchange (IDX), Shenyang Commercial City, Hong Kong Stock Exchange, London Stock Exchange and the Nasdaq Composite. The results show a significant sign in the capital market performance seen from the composite stock price index (CSPI) and a strong correlation to the five stock markets. in another hand, the result of research seen from the return of the market shows no significant differences due to the contagion effect that leads to a relationship or capital market interactions that make up a capital market integration. Keyword; Capital market performance, Composite Stock Price Index (CSPI), and Return Market.